Natural Resources and Economic Growth: A Meta-Analysis - Tomas Havranek; Roman Horvath; Ayaz Zeynalov (Charles University in Prague, Institute of Economic Studies (IES), 2016)
An important question in development studies is how abundance of natural resources affects long-term economic growth. No consensus answer, however, has yet emerged, with approximately 40% of empirical papers finding a negative effect, 40% finding no effect, and 20% finding a positive effect. Does the literature taken together imply the existence of the so-called natural resource curse? In a quantitative survey of 402 estimates reported in 33 studies, we find that overall support for the resource curse hypothesis is weak when potential publication bias and method heterogeneity are taken into account. Our results also suggest that three aspects of study design are especially effective in explaining the differences in results across studies: 1) including an interaction between natural resources and institutional quality, 2) controlling for the level of investment activity, and 3) distinguishing between different types of natural resources.
Keywords: Q30; O13; C51; 330; natural resources; economic growth; institutions; publication selection bias; meta-analysis